Possíveis territorialidades e a produção crítica da arte suturas e sobrejustaposições entre vestes sem corpos e corpos sem vestes - Mossi, Cristian Poletti (2010)
The present dissertation is in line of research Arts and Culture, it aims at investigating the subjective processes that can occur from the suture and sobrejuxtaposition (understood as instrumental concepts which share the same time the idea of the sobre-juxtaposition and overlapping) images of works by Claudia Casarino (installation, untitled, 2005) bringing clothes without bodies, which I call "corporate dress" and Vanessa Beecroft s (performance, vb45, 2001) proposing bodies without clothes, which I named 'out-of-subject bodies'. To consolidate the process were discussed such images within the concepts of territory and critical production of art to make sense together some of the contemporary theories that graze the question of body, subjectivity and garments - understood here as possible territoriality. To this end, built up over the search a visual diary that brings verbal (written) and visual (drawings and collages) notes that dialogue throughout the text with images of the works in question. The work is divided into three main areas in which we discuss primarily the method and context that protested the job, then the images will be finally considered separately to think about possible sutures and juxtapositions between them. Therefore, in Casarino s they are faced with objects that get animated through our eyes. Shadows and robes dancing, though still in the room where the work is installed and refer to this body-absent. On the other hand, in Beecroft s it can be found bodies that present the possibility of life and movement, are static, apathetic, oddly organized as things. Make up a kind of installation with objects/bodies that generate disappearances are against each other. If the body and, by analogy, the garment can be thought of as regions, we can infer that Casarino s work is the land, but the occupants of the land and perhaps a spectral presence implies that the bodies they have embodied or would embody. In Beecroft s work, their bodies get out of the subjectivity and the extent is presented repeatedly naked, hence dispossessed, believing that such territory discards to make another kind of territory without borders.